ANALYSIS OF THE APPLICATION OF THE CAMELS METHOD TO MEASURE THE LEVEL OF HEALTH AT BANK MEGA SYARIAH FOR PERIOD 2019-2023 - Nur Cahyani, Della; Khasanah, Faizatun; Auliyaun Nisaa, Mufida; Iqbal Surya Pratikto, Muhammad; Adam Bin Hamzy, Muhammad (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research aims: This study aims to assess the financial health of Bank Mega Syariah during the 2019–2023 period using the CAMELS framework, to determine its performance stability and risk exposure. Design/Methodology/Approach: This research employs a quantitative descriptive approach based on secondary data extracted from the annual financial reports of Bank Mega Syariah (2019–2023). The analysis is conducted using the CAMELS method, which evaluates six key aspects: Capital Adequacy, Asset Quality, Management, Earnings, Liquidity, and Sensitivity to Market Risk. The performance of Bank Mega Syariah is ranked relative to other Islamic banks operating in Indonesia. Research findings: The results show that Bank Mega Syariah consistently maintained a sound financial position throughout the five-year period. The bank ranked first in key indicators such as Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Operational Efficiency Ratio (BOPO), and Financing to Deposit Ratio (FDR). Additionally, it ranked second in Return on Assets (ROA) and Net Income (NI), and third in Net Operating Income (PDN), though it placed fourth in Return on Equity (ROE). Theoretical Contribution/Originality: This study contributes to the limited body of empirical literature on Islamic bank performance in Indonesia by offering a multi-year evaluation using the comprehensive CAMELS framework. It enhances understanding of Islamic bank resilience and performance indicators under Sharia compliance. Practitioners/Policy Implications: The findings provide useful insights for bank management, investors, and regulators to support strategic decision-making, risk mitigation, and regulatory supervision. They also highlight the importance of maintaining balanced financial ratios to ensure long-term sustainability. Research Limitations/Implications: The analysis is limited to one Islamic bank and relies solely on publicly available financial reports, without incorporating macroeconomic variables or customer perception data. Future research could expand the scope to include comparative studies across multiple Islamic banks or introduce qualitative dimensions.